IMPLEMENTING A DIGITAL LEARNING MEDIA POLICY TO SUPPORT ELEMENTARY SCHOOL STUDENTS' LEARNING MOTIVATION: A CASE STUDY AT SDN 001 BARONG TONGKOK - Peronika; Agus Sholahuddin; Wahyu Wiyani (PT. Antis International Publisher, 2026)
Objective: This study examined the implementation of the policy on digital learning media use at SDN 001 Barong Tongkok, Kutai Barat Regency, with particular attention to instructional planning, instructional implementation, learning process assessment, and its perceived contribution to students' learning motivation under Permendikbudristek Number 16 of 2022. Method: A qualitative descriptive design was employed with 13 informants, including the principal, teachers, the school operator, and education staff. Data were collected through semi-structured interviews, classroom observations, questionnaires, and documentation. Questionnaire responses were summarized using frequencies and percentages to support qualitative interpretation. Results: Policy implementation was generally perceived positively. In instructional planning, 10 informants (76.92%) strongly agreed and 3 (23.08%) agreed; in instructional implementation, 11 (84.62%) strongly agreed and 2 (15.38%) agreed; and in learning process assessment, 9 (69.23%) strongly agreed, 3 (23.08%) agreed, and 1 (7.69%) disagreed. Digital media were perceived to support students' interest, attention, enthusiasm, confidence in asking and answering questions, persistence, and classroom participation. Supporting factors included principal leadership, teacher competence and innovation, digital facilities, internet access, technical assistance, parental and school committee support, and positive student responses. Barriers included insufficient devices, unstable internet connectivity, uneven teacher competence, limited preparation time, differences in students' digital literacy, budget constraints, and inconsistent use across classrooms. Novelty: By integrating policy implementation, instructional processes, organizational capacity, and student motivation within a single elementary school case, this study shows that meaningful digital learning depends on leadership, teacher capacity, technical support, and institutional consistency rather than on technology availability alone.